EVALUASI OUTPUT KEBIJAKAN DANA DESA UNTUK PEMBANGUNAN FASILITAS KESEHATAN DI KECAMATAN SUKOREJO, KABUPATEN KENDAL - Wildan Nur Aiman; Sutopo Patria Jati; Septo Pawelas Arso (Jurnal Kesehatan Masyarakat (Undip), 2018)
This study aims to evaluate the output of village funds’ policy for developing health facilities in Sukorejo Subdistrict Kendal Regency. The research uses qualitative descriptive design. The research was conducted by interviewing 17 informants involved in the implementation of village funds’ policy in Sukorejo Subdistrict, Kendal Regency. The data is collected using in-depth interview, observation and document review techniques. Data analysis technique consist of four stages which is collecting data, data reduction, data presentation and conclusion making. Source triangulation presents to test the validity of the data. The result shows that based on accessibility indicator, Polindes in Kalipakis and Trimulyo Villages are strategic and easily accessible by the community. The deviation is not found in Kalipakis Village, contrasting Trimulyo Village in which Polindes lacks of equipment. The service accuracy indicator shows good result for both Kalipakis Village and Trimulyo Village in which the funds got into the village accounts, owned by each village’s government, on time, in addition, the process of constructing and its finishing done based on timeline. The accountability indicator shows good result for both Kalipakis Village and Trimuyo Village as the inspectorate, the institution to examine the use of village funds in Kendal Regency, gives positive review on SPJ in Kalipakis Village and Trimulyo Village. And last, based on conformity with needs indicators, Kalipakis Village and Trimulyo Village have good result because Polindes was successfully proposed as community needs in musrenbangdes in 2016.